Peran Komunikasi Positif Orang Tua Dalam Meningkatkan Children Well-Being Anak Usia Dini - Risa Muplihah; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to analyze the role of positive parental communication in improving children’s well-being in early childhood. Positive communication refers to interactions that emphasize empathy, supportive language, and respectful responses to children’s feelings. Children’s well-being encompasses a holistic condition that includes emotional, social, and psychological aspects of child development. This research employed a qualitative approach using a literature review method. Data were obtained from various scientific sources, including national and international journals relevant to the research topic. The findings indicate that consistently applied positive communication can enhance children’s sense of security, self-confidence, and ability to regulate emotions. Furthermore, supportive communication strengthens the emotional bond between parents and children, which positively influences children’s psychological well-being. According to Harter (2012), emotional support from close environments plays an essential role in shaping children’s positive self-perception (p. 87). Therefore, positive parental communication is considered an important factor in supporting the optimal achievement of children’s well-being in early childhood